A bidirectional neural interface CMOS analog front-end IC with embedded isolation switch for implantable devices. (December 2016) - Abdi, Alfian; Cha, Hyouk-Kyu
Abstract: A bidirectional neural interface analog front-end IC with both stimulation and recording functions is implemented using 0.18-µm standard CMOS process. The proposed IC is comprised of a bipolar biphasic neural stimulator using a transistor-stacked current-mirror driver to achieve good current matching performance in stimulation mode and low-voltage capacitive feedback neural amplifiers for recording mode. In order to save die area, high-voltage isolation switches are embedded within the stimulator core to protect the low-voltage recording circuits from damage. Despite using a low-voltage process, the stimulator is able to deliver up to 1 mA current through 10 kΩ load using 12.8 V supply voltage and the recording amplifier uses 0.8 V supply voltage while consuming 1 µA of current. The complete IC occupies 0.29 mm 2 of die area and can be applied for various multi electrode array interface bidirectional neural SoCs in medical implant devices.